Implementation of the Multiple Intelligence Research Program in Realizing Outstanding Students in the Field of Tahfidz Al-Qur'an at Al-Aqobah 4 Diwek Jombang Pesantren - Amalia, Amalia; Hosna, Rofiatul (Pusdikra Publishing, 2024)
Islamic boarding schools in the digital and modern era must develop knowledge for students to keep up with the rapid technological advancements, while ensuring that students are nurtured according to their individual intelligences, all within the framework of Islamic teachings. A kyai (Islamic scholar) must understand the diverse intellectual characteristics of students and guide them based on their interests and talents. Traditionally, students in Islamic boarding schools often master only one field of knowledge, such as Fiqh, Hadith, or the Quran. The multiple intelligences research program is one way to create successful students by recognizing that every individual has different types of intelligence. This qualitative research uses a case study approach to explore the implementation of the multiple intelligences program at Al-Aqobah 4 Islamic Boarding School in Diwek, Jombang, specifically in helping students excel in Quran memorization (tahfidz). Data was collected through interviews, observations, and documentation, and analyzed using domain and taxonomic analysis. The findings suggest that the multiple intelligences program can run effectively, helping students find memorization methods that suit their individual tendencies or intelligence types, thereby improving their ability to memorize the Quran more efficiently.